Underlying Co-Morbidity Reveals Unique Immune Signatures in Type II Diabetes Patients Infected With SARS-CoV2 - Sengupta, Soumya; Bhattacharya, Gargee; Chatterjee, Sanchari; Datey, Ankita; Shaw, Shubham K.; Suranjika, Sandhya; Nath, Paritosh; Barik, Prakash K.; Prasad, Punit; Chattopadhyay, Soma; Swain, Rajeeb K.; Parida, Ajay; et al. (Frontiers in Immunology, 2022)
Background: SARS-CoV2 infection in patients with comorbidities, particularly T2DM has been a major challenge globally. Here, we did whole blood immunophenotyping along with plasma cytokine, chemokine, antibody isotyping and viral load determination from oropharyngeal swab to understand the immune pathology in the T2DM patients infected with SARS-CoV2. Methods: Blood samples from 25 Covid-19 positive patients having T2DM, 10 Covid-19 positive patients not having T2DM and 10 Covid-19 negative, non-diabetic healthy controls were assessed for various immune cells by analyzing for their signature surface proteins in mass cytometry. Circulating cytokines, chemokines and antibody isotypes were determined from plasma. Viral copy number was determined from oropharyngeal swabs. All our representative data corroborated with laboratory findings. Results: Our observations encompass T2DM patients having elevated levels of both type I and type II cytokines and higher levels of circulating IgA, IgM, IgG1 and IgG2 as compared to NDM and healthy volunteers. They also displayed higher percentages of granulocytes, mDCs, plasmablasts, Th2-like cells, CD4+ EM cells, CD8+ TE cells as compared to healthy volunteers. T2DM patients also displayed lower percentages of pDCs, lymphocytes, CD8+ TE cells, CD4+, CD8+ EM. Conclusion: Our study demonstrated that patients with T2DM displayed higher inflammatory markers and a dysregulated anti-viral and anti-inflammatory response when compared to NDM and healthy controls. Contribution to the field: Covid-19 infection in people with comorbidities, particularly T2DM has been a cause of mortality in several nations and they represent an extremely vulnerable population to Covid-19. This study is one of the most comprehensive study from India, to understand the interplay between immune response and viremia occurring in these T2DM patients infected with SARS-CoV2 and will help in designing public health response and vaccination priorities.